Features the in investigation initially investigating computer crimes - Верченко, Вадим Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
This article discusses some common mistakes that are often made while carrying out investigations inrelation to computer data and computers themselves and recommendations for their elimination.